Synthetic Approaches to 1,3,4-Oxadiazole-Containing Boronic Derivatives - Barbara Wołek; Agnieszka Kudelko (Applied Sciences, 2025)
1,3,4-Oxadiazoles containing boronic acid moieties are promising as a highly versatile class of compounds with significant utility across various scientific domains. The diverse synthetic methodologies for their preparation make these compounds valuable precursors for developing novel entities with tailored properties in medicinal chemistry, agrochemistry, and materials science. This review systematically compiles and discusses synthetic methods for the direct and indirect incorporation of boronic acid derivatives into 1,3,4-oxadiazole scaffolds. Understanding these strategies is particularly important because of their key role in modern synthetic transformations, especially Suzuki–Miyaura cross-coupling reactions, which enable easy access to a new generation of structurally diverse 1,3,4-oxadiazole-based compounds. The synthetic procedures and reactions discussed are based on the currently available literature, offering a comprehensive overview of this rapidly evolving field.